Culm Characteristics of Yellow Bamboo (Bambusa vulgaris var. striata) from Private Forest in Sleman Regency, Yogyakarta - Budi Mulyana; Rina Reorita (Journal of Sylva Indonesiana, 2022)
Sleman Regency has determined bamboo as a superior non-timber forest product. Yellow bamboo (Bambusa vulgaris var. striata) is usually used for construction and craft materials. Hence, it is necessary to understand the characteristics of the culm. The study aimed to determine the predictor variables for the total internodes, and the distribution pattern of the length and bamboo wall thickness of the internodes on the yellow bamboo culms. The method used in this research was the method of destructive sampling for 30 bamboo culm samples. The samples were measured using a caliper for diameter at breast height and wall thickness, and measurement tape for the total length of the bamboo culm. For detail measurement, each sample was cut for each internode to be measured the length, diameter, and wall thickness of the internodes. The results showed that the predictor of diameter at breast height (dbh) is a predictor in estimating the total number of internodes on the culm resulting in an R2 of 0.631. While the total culm height as a predictor was able to explain the total number of internodes with an R2 value of 0.692. The length of the internodes pattern on the yellow bamboo culm from the bottom to the top side formed a bell curve. In the middle area of the culm, the length of the internode increased, but then it shrank back to the top side. The diameter and wall thickness patterns of the internode were non-linear. In addition, the predictors of diameter at breast height and total height are less accurate to explain the total number of internodes in yellow bamboo culms.